Perspectives for monocyte/macrophage-based diagnostics of chronic inflammation - Kzhyshkowska, Julia; Gudima, Alexandru; Moganti, Kondaiah (Transfusion medicine and hemotherapy, 2016)
Low-grade chronic inflammation underlies the development of the most dangerous cardiometabolic disorders including type 2 diabetes and its vascular complications. In contrast to acute inflammation induced by bacteria and viruses, chronic inflammation can be driven by abnormal reaction to endogenous factors, including Th2 cytokines, metabolic factors like advanced glycation end products (AGEs), modified lipoproteins, or hyperglycemia. The key innate immune cells that recognize these factors in blood circulation are monocytes. Inflammatory programming of monocytes which migrate into tissues can, in turn, result into generation of tissue macrophages with pathological functions. Therefore, determination of the molecular and functional phenotype of circulating monocytes is a very promising diagnostic tool for the identification of hidden inflammation, which can precede the development of the pathology. Here we propose a new test system for the identification of inflammatory programming of monocytes: surface biomarkers and ex vivo functional system. We summarize the current knowledge about surface biomarkers for monocyte subsets, including CD16, CCR2, CX3CR1, CD64, stabilin-1 and CD36, and their association with inflammatory human disorders. Furthermore, we present the design of an ex vivo monocyte-based test system with minimal set of parameters as a potential diagnostic tool for the identification of personalized inflammatory responses.